The CpxR/CpxA system contributes to Salmonella gold-resistance by controlling the GolS-dependent gesABC transcription - Cerminati, Sebastián (2017)
Several regulatory systems contribute to bacterial resistance to heavy metals controlling the expression of factors required to eliminate the intoxicant and/or to repair the damage caused by it. In Salmonella, the response to Au ions is mediated by the specific metalloregulator GolS that, among other genes, controls the expression of the RND-efflux pump GesABC. In this work, we demonstrate that CpxR/CpxA, a main cell-envelope stress-responding system, promotes gesABC transcription in the presence of Au ions at neutral pH. Deletion of either cpxA or cpxR, or mutation of the CpxR-binding site identified upstream of the GolS-operator in the gesABC promoter region reduces but does not abrogate the GolS- and Au-dependent activation of gesABC. Au also triggers the activation of the CpxR/CpxA system and deletion of the cpxRA operon severely reduces survival in the presence of the toxic metal. Our results indicate that the coordinated action of GolS and CpxR/CpxA contribute to protecting the cell from severe Au damage.